2020
DOI: 10.1002/prot.25957
|View full text |Cite
|
Sign up to set email alerts
|

Numerous severely twisted N‐acetylglucosamine conformations found in the protein databank

Abstract: Taking advantage of the known planarity of the N‐acetyl group of N‐acetylglucosamine, an analysis of the quality of carbohydrate structures found in the protein databank was performed. Few obvious defects of the local geometry of the carbonyl group were observed. However, the N‐acetyl group was often found in the less favorable cis conformation (12% of the cases). It was also found severely twisted in numerous instances, especially in structures with a resolution poorer than 1.9 Å determined between 2000 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Similar to in a peptide, the bond between N2 and C7 has a bond order higher than 1. As a result, the atoms in the plane can take on a cis - and a trans -conformation with a strong preference for the latter [ 45 ]. The possibility of having two conformations is described in several ways: AceDRG splits the plane into 2 sections and defines the N2-C7 bond as rotatable with target values at 0° and 180°.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to in a peptide, the bond between N2 and C7 has a bond order higher than 1. As a result, the atoms in the plane can take on a cis - and a trans -conformation with a strong preference for the latter [ 45 ]. The possibility of having two conformations is described in several ways: AceDRG splits the plane into 2 sections and defines the N2-C7 bond as rotatable with target values at 0° and 180°.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, most of the data obtained on the basis of crystallographic experiments can dramatically differ from glycan conformations in solution or have poor resolution which needs further adjustment [ 299 , 300 ]. Moreover, not all of the objects of interest can be obtained as a single crystal.…”
Section: Experimental Data Validationmentioning
confidence: 99%
“…Another issue of concern related to Protein Data Bank is large proportion of errors in deposited coordinates, leading to requirement for a thorough checkup and development of data remediation services [ 319 ]. Commonly occurring problems associated with nomenclature, poor glycan geometry, linkage errors, missing or surplus atoms can seriously decline the quality of the obtained 3D structures [ 300 , 320 , 321 ]. Using Privateer software, it was discovered [ 299 ],[ 301 ] that PDB deposits significant number of erroneous N-glycosylated structures with pyranose ring distortions, considering preferred adoption of 4 C 1 conformation for D-sugars and 1 C 4 conformation for L-sugars ( Figure 9 ).…”
Section: Protein Data Bank and Its Validationmentioning
confidence: 99%
“…Prior studies show that the amide bond in GlcNAc is predominantly in the trans conformation (the relative orientation of C2 and C2', see Scheme 2), with only about 1.8 % in the cis conformation at 42 °C. [9] However, surveys on glycoprotein X-ray crystal structures found that as much as 6-12 % of the GlcNAc residues populate the cis conformation, [9,15] although a substantial amount of these structures are severely twisted or may be due to an erroneous interchange of the carbonyl oxygen and the methyl carbon, which indicates an overestimation of the amount of cis conformations. [15,16] Thus the amide cis conformation may play an important role in certain glycoconjugates, although characterization of the cis form in monomeric GlcNAc remains challenging due to the low abundance in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[9] In this study, the amide protons of the GlcNAc cis forms were observed for the first time and amide protons of both cis and trans forms were investigated by NMR spectroscopy. A series of NMR experiments were utilized to measure J-couplings within the N-acetyl group of uniformly 13 C, 15 N-labeled GlcNAc. 13 C, 15 N-labeling enabled the measurement of eight vicinal scalar coupling constants (one 3 J HH , three 3 J CC , and four 3 J CH ) within the N-acetyl group, of which six are sensitive to the θ 1 angle and two are sensitive to the θ 2 angle (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%